Eyeworms of wild birds and new record of Thelazia (Thelaziella) aquilina (Nematoda: Spirurida) - Renata Fagundes-Moreira; Marcos Antonio Bezerra-Santos; Riccardo Paolo Lia; Cíntia Daudt; Juliana Tessália Wagatsuma; Elaine Christina Oliveira de Carmo; Laura Berger; Flavio Roberto Chaves da Silva; João Fabio Soares; Domenico Otranto (International Journal for Parasitology: Parasites and Wildlife, 2024)
The eyeworms of the subgenus Thelaziella infect orbital cavities, conjunctival sacs and lachrymal ducts of many wild birds, being able to cause conjunctivitis. In Brazil, at least 10 species of Thelaziella have been described. Here we present a brief review of cases of Thelazia (Thelaziella) aquilina and describe the infection of this parasite in Harpia harpyja, as a new host record. Two nematodes were collected from the surface of the cornea of an adult female H. harpyja in the Amazon region (Brazil) and were morphologically identified as two males of T. (T.) aquilina. This data demonstrated the need for further studies focused on elucidating the transmission, biological cycle, and phylogenetic positioning of Thelaziella as subgenus.